السخرية في شعر أبي الحسين الجزار "601هـ - 679هـ": دراسة في الرؤية والتشكيل الفني - حسب الله، بهاء عبدالفتاح على (جامعة الأزهر - كلية اللغة العربية بجرجا, 2021)
يتناول هذا البحث ظاهرة السخرية عند مبدع من أبرز شعراء العصر المملوكي في القرن السابع الهجري، ألا وهو أبو الحسين الجزار (601 هـ-679هـ)، ويقف البحث بصفة تأصيلية عند ظاهرة السخرية في الشعر العربي القديم منذ العصر الجاهلي ومرورا بالعصور الثلاثة الإسلامي والأموي والعباسي، ووصولا إلى الفترة الوسيطة؛ فترة الشاعر نفسه، وتحديدا في العصر المملوكي الأول، وربطت الدراسة بين نشأة الجزار وطبيعة حرفته كجزار وما ترتب عليه من بزوغ ملامح السخرية في شعره على أثر حرفته، وتوسعه فيها على أكثر من محور، منها محاور النقد المجتمعي، والسخرية من الفقر والعوز والحاجة، ومن معاملة الناس وجور الزمان وعصف الأيام. وقد صبغ الجزار موضوعية سخريته بالعديد من الملامح الفنية منها؛ ملامح لغته وبنية أساليبه، وميله إلى لغة الحكي والقص والترادف المعنوي في سياق النص والتكرار اللفظي والمقاربة السياقية بين حدود معاني الشكوى والسخرية والعوز والفقر، بتوظيف اللغة الاستدرارية والاجترارية والحكاءة، كذلك حرصه على ربط تلك المعاني وبنياتها اللغوية شديدة الخصوصية بالمجاز وبنيات الصور الخيالية والفنية، حتى غدت الصورة عنده مبتكرة وأحيانا غريبة أو نادرة من باب إثارة القوة المتخيلة عند المتلقي، والأمر نفسه في انعكاس معانيه على جدليات التكرار الصوتي والمعنوي والبديعي والإيقاعي، وربطه بواقعه النفسي والاجتماعي والذاتي، وبتراكيب نصوصه غير المعقدة مما جعلنا أم عدة ركائز من ركائز فنه وإبداعه في سياق موضوعه الساخر والهزلي."
This research deals with the phenomenon of irony by a creative one of the most prominent poets of the Mamluk era in the seventh century AH, namely Abu Al-Hussein Al-Jazzar (601 AH - 679 AH). The research is rooted in the phenomenon of irony in ancient Arabic poetry since the pre-Islamic era and passing through the three Islamic, Umayyad and Abbasid eras Up to the intermediate period; The period of the poet himself, specifically in the first Mamluk era, and the study linked the emergence of the butcher to the nature of his craft as a butcher and the consequence of the emergence of the features of irony in his poetry as a result of his craft, and his expansion in it on more than one axis, including the axes of societal criticism, mockery of poverty, need and need, and from Treating people, unfair time and storming days. Al-Jazzar painted the objectivity of his sarcasm with many artistic features, including: The features of his language and the structure of his methods, his tendency to the language of narration, storytelling and moral synonymy in the context of the text and verbal repetition and the contextual approach between the limits of the meanings of complaint, irony, want and poverty, by employing rotational and ritualistic language and storytelling, as well as his keenness to link those meanings and their very specific linguistic structures with metaphors and structures of imaginary and artistic images, even His image has become innovative and sometimes strange or rare in order to evoke the imagined power of the recipient, and the same is in the reflection of his meanings on the dialectics of phonological, moral, apparent and rhythmic repetition, and linking it to his psychological, social and subjective reality, and to the uncomplicated structures of his texts, which made us the mother of several pillars of his art and creativity in a context Its satirical and comic subject."
Keywords: الظواهر السخرية -- الشعر العربي -- الجزار، أبي الحسين، ت. 679 هـ